Art and Education - Wojnar, Irena (Pedagogische Studiën, 1973)
Two contradictory views on art and its role inthe life of man have existed, or to be more precisecoexisted with each other, since the oldesttimes. An opinion was formulated in ancientGreece that art serves for 'embelUshment ofhuman souls'; but at the same time it waspromulgated that art is but a 'sublime Madness',dangerous for the internal harmony of man.Sometimes art was to be the source of internalpurification and sometimes merely a lighthearted amusement. It was believed that artcan serve as a valuable 'handbook of life', andsimultaneously it was considered to be adangerous 'manufacturer of illusions', an attemptat constructing life only within the dimensionof imagination, being thus contradictory toreal life. A history of opinions about art regarding its place and role in the life of man and society has not yet been written; nor can we say thatinnovative experiments undertaken from ancient times tili our own day and aiming atsubstantiating education values and possibilitiesof art have been registered in an exhaustive way.Nevertheless numerous studies of a monographicor contributive character have drawn attentionto the richness of reflections on art and educationas well as varied signs of practical initiativeconnected with the evolution of aesthetic education. Pythagoras, Plato, and Aristotle opena long list of theoreticians who have supportedthis trend. Many years later Friedrich Schiller,John Ruskin and William Morris, NikolayCzemyshewski and Lev Tolstoy, John Dewey andHerbert Read joined their numbers. The namesof pedagoguepracticians are less known. Vittorino da Feltre remained a lonely pioneer for along time and it was only in the nineteenthCentury that the number of practical actions which are so rieh in our contemporary epoch was multiplied. Corrado Ricci and Franz Cizek,Emile JaquesDalcroze and Celestin Freinetwent down in this contemporary history asimportant names.